Encryption method of IPV6 network discovery protocols security / Ummi Syahirah Mohd Daud - Mohd Daud, Ummi Syahirah (2019)
Nowadays, there are many devices that have connection with internet and this has led to an increasing usage of IP address. IPv4 have slowly reached to an end which led to introduction of IPv6 protocol. IPv6 protocol include Neighbor Discovery Protocol (NDP) for configuration IP address that make it easier to use compare to IPv4. Even though, IPv6 have NDP but still there are few drawbacks to NDP protocol which can lead to network failure. The downside of NDP protocol can make IPv6 fall for some vulnerabilities such as Man in The Middle (MiTM), Denial of Service (DoS) and other problems. For example, a malicious router will claimed itself as a default router in network to run MiTM. Before this, there are many protocols to prevent NDP problem such as RA Guard/DHCPv6 Guard and Secure Neighbor Discovery (SEND). However, these protocol fail to protect NDP. This project is to analyse the encryption method used in IPv6 network.